Stride Length and Torso Biomechanics As They Relate To Medial Elbow Injuries In Adolescent Aged Baseball pitchers: A Clinical Commentary - Zachary Dietz; Dylan DeWeese; Neil Shaw; Cody Huth; Jacob Ball; Victoria Reeves; Ryan Monti; Ryan Bitzel (International Journal of Sports Physical Therapy)
There is a limited amount of literature examining torso biomechanics and stride length while addressing their relationship to medial elbow injuries in the adolescent baseball pitcher. Anatomical changes, growth, early sport specialization, multiple team participation, mound distance, mound height, and high pitch counts place adolescent pitchers at an exceptionally higher risk for medial elbow injuries. Existing evidence indicates that decreased stride length and altered trunk rotation is correlated with increased medial elbow loading for the adolescent overhead athlete. Further research is required to quantify adequate parameters for torso kinematics, control, and their correlation to stride length, in order to positively affect the biomechanical transfer of energy and potentially prevent injuries during the overhead throwing motion. The purpose of this clinical commentary is to examine and summarize the role of torso biomechanics and stride length in relation to medial elbow injuries in adolescent baseball pitchers.